The Study of Consumers Purchase Intention and Preference Analysis Towards Bottled Coffee Product in Bandung - Resty Nabila, Regina; Aprilianty, Fitri (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Coffee Industry is one of Food and Beverage Industry that always increase continuously, especially in Bandung. Nowadays, coffee is become a life style and popular either in Global or Indonesia. The competition in Coffee Industry is tend to be high, to keep the sustainability of Demitasse Company, they want to produce new product which is bottled coffee product. This research is helping Demitasse Company to generate the information about how the relation between consumer perception, pereference, attitude, and purchase intention towards bottled coffee product. The data Collection is generated by interview and questionnaire with 400 respondents. The result of the data collection was analyzed by partial least square method. This research shows how the relation between consumer perception, consumer attitude and purchase intention towards bottled coffee product. The end of this research shows that there is a positive relation between consumer perception, consumer attitude and purchase intention.Â Keywords: Consumer Perception, Consumer Attitude, Consumer Preference, Purchase Intention.